2020
DOI: 10.1038/s41419-020-2654-2
|View full text |Cite
|
Sign up to set email alerts
|

BIK drives an aggressive breast cancer phenotype through sublethal apoptosis and predicts poor prognosis of ER-positive breast cancer

Abstract: Apoptosis is fundamental to normal animal development and is the target for many anticancer therapies. Recent studies have explored the consequences of “failed apoptosis” where the apoptotic program is initiated but does not go to completion and does not cause cell death. Nevertheless, this failed apoptosis induces DNA double-strand breaks generating mutations that facilitate tumorigenesis. Whether failed apoptosis is relevant to clinical disease is unknown. BCL-2 interacting killer (BIK) is a stress-induced B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 79 publications
(130 reference statements)
2
16
0
2
Order By: Relevance
“…As uncovered in the past investigations, apoptosis in PTC is a multifaceted and multistep process. Apoptosis based biomarkers have also been proposed for many other cancers (17)(18)(19)21,22). Despite the fact that the role of genes and their associated proteins such as Fas/FasL, Bcl-2 family, p53, and others have been exhibited in PTC malignant growth, our comprehension of the collaboration between these molecules is still poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As uncovered in the past investigations, apoptosis in PTC is a multifaceted and multistep process. Apoptosis based biomarkers have also been proposed for many other cancers (17)(18)(19)21,22). Despite the fact that the role of genes and their associated proteins such as Fas/FasL, Bcl-2 family, p53, and others have been exhibited in PTC malignant growth, our comprehension of the collaboration between these molecules is still poor.…”
Section: Discussionmentioning
confidence: 99%
“…Another review provides extensive information related to apoptotic biomarkers such as p53, Bcl2, Fas/FasL, TRAIL in colorectal cancer (18). Several other studies have also identified key molecules with prognostic roles in other cancers like gastric cancer (19,20), breast cancer (21), lung cancer (22), bladder urothelial carcinoma (23), glioblastoma (24) and osteosarcoma (25). Apoptosis has also been found to have a crucial role in carcinogenesis of thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to varied expression of pro-survival proteins such as IAPs or Bcl-2 family members between the different cell types used in these studies, which may influence whether or not cells tolerate and recover from mitochondrial damage [ 172 ]. Minority MOMP and associated caspase/CAD-dependent mutagenesis was also implicated upon expression of the BH3-only protein BIK [ 173 ]. BIK-expressed or staurosporine-treated cells with low and high levels of caspase activity were sorted and clonogenic potential determined.…”
Section: Mutagenic Consequences Of Apoptotic Signalingmentioning
confidence: 99%
“…BIK-expressed or staurosporine-treated cells with low and high levels of caspase activity were sorted and clonogenic potential determined. Colonies failed to form following staurosporine exposure regardless of caspase levels, whereas at least 50% of cells maintained clonogenicity after BIK expression and caspase activation, implying partial MOMP within viable cells [ 173 ].…”
Section: Mutagenic Consequences Of Apoptotic Signalingmentioning
confidence: 99%
“…Recently, it was demonstrated that radiotherapy, chemotherapeutic drugs or BH3‐only proteins such as BCL2‐interacting killer (BIK) can activate caspases at nonlethal levels in surviving cells following minority MOMP [ 82 , 83 , 84 ]. Despite the fact that these studies proposed different DNA damaging mechanisms (Caspase‐Activated DNAse or CAD and endonuclease G, EndoG, respectively), they all reported that surviving cells are heavily impacted by unresolved DNA damage leading to genomic instability and tumorigenesis (Fig.…”
Section: How Failed Apoptosis Shapes Cancer Aggressivenessmentioning
confidence: 99%